Sierra Leone : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2004)
This Selected Issues paper examines recent economic developments in Sierra Leone. The paper highlights that the economic recovery in Sierra Leone has benefited especially from the extensive rehabilitation and humanitarian activities in liberated areas. Real GDP growth rose by 4 percent in 2000 and accelerated further in 2001 and 2002. The paper lays out some conceptual issues for the analysis of government debt sustainability, and discusses key issues related to long-term fiscal sustainability. The challenges ahead for rehabilitating Sierra Leone's mining sector are also examined.